New Data of Morphological Variation in Microhyla gadjahmadai Atmaja et al., 2018 (Anura: Microhylidae) from West Sumatra - Shinta Triana Putri; Rijal Satria; Reki Kardiman; Fitra Arya Dwi Nugraha (Jurnal Biologi Tropis, 2023)
Microhyla gadjahmadai was first described by Atmaja et al. in 2018. For the newly described species category, there is not much information explaining this species and there has been no further research after this species was described, especially in West Sumatra. This study aims to provide information on variations in the morphological characteristics of M. gadjahmadai in West Sumatra, through morphological and morphometric analysis of 8 samples (1 adult male and 7 adult females) found in Puncak Anai (Dempo Anailand), Kanagarian Guguak, District 2x11 Timber Planting, Padang Pariaman Regency, West Sumatra. This study used the Visual Encounter Survey (VES) method. The result of the present study shows that no significant morphological differences between the holotype and paratype of Microhyla gadjahmadai and other specimens from West Sumatera. However, the present study reported that the morphological variations of this species.